KARAKTERISTIK MINYAK NILAM HASIL FUSI PROTOPLAS ANTARA NILAM ACEH DENGAN NILAM JAWA - Yang Nuryani (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
Oil characterization of somatic hybrids resulted from protoplast fusion between Aceh patchouli (Pogostemon cablin Benth.) Sidikalang and TT 75 and Java patchouli(Pogostemon heyneanus Benth.) Girilaya, was conducted at the laboratory of Indonesian Spices and Medicinal Crops Research Institute (ISMECRI) in March, 2003. The results showed that out of 13 somatic hybrids, two hybrids namely 9 II 8 and 9 II 21 (somatic hybrids between Girilaya and TT 75) have oil content (2,91% and 2,74% respectively), higher than that of parent TT 75 (2,09%). All somatic hybrids have higher than 30% patchouli alcohol content (minimum level of export quality). The number 9 II 21 showed the highest patchouli content (39,11%).